Comparison of the hypoglycemic effect of sitagliptin versus the combination of mitiglinide and voglibose in drug-naïve Japanese patients with type 2 diabetes. (December 2013) - Ohta, Akio; Ohshige, Toshihiko; Sakai, Kensuke; Nakamura, Yuta; Tenjin, Ayumi; Tsukiyama, Shuichi; Terashima, Yuko; Matsubara, Fumiaki; Kawata, Takehiro; Nagai, Yoshio; Tanaka, Yasushi
Abstract : Objective: The postprandial glucose (PPG) level is reduced by α-GIs, glinides and DPP4Is through different pharmacological actions. The aim of this study was to compare the effect of sitagliptin (S) versus that of the combination of mitiglinide and voglibose (M+V) on markers of glycemic control. Research design and methods: A randomized cross-over trial was performed in 20 patients with drug-naïve type 2 diabetes. The patients were randomized to receive S (50 mg/day) or M+V (1 tablet 3 times daily). Treatment was continued for 8 weeks, after which they were switched to the other regimen and treated for another 8 weeks. At baseline, after the first regimen, and after the second regimen, a meal test was performed. Main outcome measures: The markers of glycemic control were examined. Results: Reduction of glucose excursion was significantly greater with M+V than with S. HbA1c did not change with either regimen. However, 1, 5-anhydroglucitol showed a significant increase from baseline with both regimens (7.9 ± 4.3 μg/ml at baseline vs. 10.6 ± 5.5 with S, p < 0.05 and 15.1 ± 6.2 with M+V, p < 0.01). Compared with baseline, glycoalbumin was significantly reduced by M+V, but not S (19.6 ± 2.9% at baseline vs. 17.3 ± 3.8% with M+V, p < 0.05). Conclusion: M+V achieved better control of PPG excursion than S.